Chemoprevention of prostate cancer with nutrients and supplements - Van Poppel H; Tombal B (Cancer Management and Research, 2011)
Hendrik Van Poppel1, Bertrand Tombal21Department of Urology, University Hospital, KU Leuven, Leuven, Belgium; 2Service d’Urologie, Cliniques Universtaires Saint Luc, Brussels, BelgiumAbstract: As the adult population is increasing, prostate cancer (PCa) will become a considerable health problem in the next millennium. This has raised public interest in potential chemoprevention of this disease. As PCa is extremely common and generally slow to progress it is regarded as an ideal candidate for chemoprevention. At present, the 5 alpha-reductase inhibitors finasteride and dutasteride have been identified as preventive agents. This review describes whether selenium, alpha-tocopherol, isoflavones, lycopene green tea polyphenols, calcium, and resveratrol may be useful for decreasing the risk of PCa in men. Although encouraging results are present, some studies show negative results. Differences in study design, sample size, dose administered, and/or concentrations achieved in the body may be the reason for these inconsistencies. Today, chemopreventive agents may be appropriate for high-risk patients like those with high-grade prostatic intraepithelial neoplasia and other high-risk groups such as patients with elevated prostate specific antigen (PSA) and negative biopsy, rapid PSA velocity, and with a family history of PCa. Although larger randomized controlled studies are needed and epidemiologic evidence should be placed in a clinical context, physicians must be aware of these preventive opportunities in PCa care. Combinations of chemopreventive agents should be carefully investigated because mechanisms of action may be additive or synergistic.Keywords: alpha-tocopherol, chemoprevention, isoflavones, lycopene, polyphenols, prostate cancer, selenium